Estrategias para una evaluación eficaz, en educación a distancia - Murrieta Vallejos, Deysi Karín (2011)
Distancelearningisanalternativewayof education but it requires a series of conditions to get a significant development and learning, without forgetting that planning and monitoring areimportantto fulfill the goals.